Malayan Railway increasing the market share of sugar and flour traffic / Anuar Mamat - Mamat, Anuar (1986)
MR has become one of the most important form of transportation for both passenger and freight. Lately the market share of MR's sugar and flour traffic has been-declining although the total production of sugar and flour is increasing over the years. MR's activities are limited to the long-haul while road transport monopolizes the short-haul movement. The main problem faced by MR in the movement of these traffic is the insufficient supply of covered wagons to the customers. Other contributory / factors are poor wagon turn round and competition terms of transit he road haulers in service and prompt settlement of loss-' and / image claims. Although , rail freight charges for sugar and flour traffic are lower than that of road(except a few), MR could not secure a larger, share since it is found that MR lacks some of the qualities in its services and facilities as mentioned earlier. Since most of the sugar and flour traffic flows are on long haul,, the MR's share of these traffic can be increased, provided MR's service qualities are improved.